Prognostic value of high-sensitivity troponin T in aneurysmal subarachnoid hemorrhage: a prospective observational study. (24th August 2019) - Guette, Pauline; Launey, Yoann; Arnouat, Matthieu; Bleichner, Jean-Paul; Masseret, Elodie; Rousseau, Chloe; Frasca, Denis; Seguin, Philippe
ABSTRACT: Objective : To evaluate the prognostic value of high-sensitivity troponin (hsT) in severe aneurysmal subarachnoid hemorrhage (aSAH). Methods : This prospective non-interventional study was performed at a surgical intensive care unit (ICU) from 2012 to 2015. Consecutive patients who had severe aSAH were included. A modified Rankin Scale score ≥ 4 or death within 3 months defined a poor outcome. hsT levels were measured at ICU admission and 72 hours following symptom onset. Results : A total of 137 patients were analyzed. The median hsT level was 29 ng/L (range: 7–4485). The best threshold level of hsT for predicting a poor outcome was 22 ng/L. At this threshold, the sensitivity was 71% (95% confidence interval [CI]: 58%-81%) and the specificity was 58% (95%CI: 46%-70%). The area under the ROC curve was 0.61 (95%CI: 0.52–0.71). Based on a multivariate analysis, the independent factors for a poor neurological prognosis were a World Federation of Neurologic Surgeons (WFNS) score ≥ 4 (odds ratio [OR]: 2.61; 95%CI: 1.04–6.56) and an hsT level > 22 ng/L (OR: 2.80; 95%CI: 1.18–6.64). Conclusion : In patients with severe aSAH, with regard for the severity of disease (assessed by the WFNS score), an hsT level > 22 ng/L at ICU admission was associated with poor outcomes.